2013
DOI: 10.1111/codi.12266
|View full text |Cite
|
Sign up to set email alerts
|

Supervised surgical training and its effect on the short‐term outcome in laparoscopic colorectal surgery

Abstract: Closely supervised training in laparoscopic colorectal surgery is not associated with any adverse effect on the short-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Also, resident participation in complex minimally invasive resections may be deemed hazardous or a risk for increased perioperative morbidity. Several studies, however, have addressed this topic and do not confirm this perception [20][21][22]. Renwick et al did not find differences in oncologic outcomes or morbidity/mortality in 344 patients operated on by residents under supervision when compared with 150 patients operated on by a staff surgeon [21].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, resident participation in complex minimally invasive resections may be deemed hazardous or a risk for increased perioperative morbidity. Several studies, however, have addressed this topic and do not confirm this perception [20][21][22]. Renwick et al did not find differences in oncologic outcomes or morbidity/mortality in 344 patients operated on by residents under supervision when compared with 150 patients operated on by a staff surgeon [21].…”
Section: Discussionmentioning
confidence: 98%
“…Also, resident participation in complex minimally invasive resections may be deemed hazardous or a risk for increased perioperative morbidity. Several studies, however, have addressed this topic and do not confirm this perception [20][21][22]. Renwick Robotically-assisted surgery further adds to the dilemma of increased complexity, as this technology has a learning curve of its own, reported at 15-30 cases in surgeons already trained in laparoscopic surgery [7].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of consultant surgeons in emergency surgeries has resulted in decreased complication rates . In studies involving colorectal resections, trainees performing surgery with the consultant mentors assisting have been shown to yield non‐inferior outcomes when compared to consultants performing the surgery themselves …”
Section: Review Of Gsa 12‐point Planmentioning
confidence: 99%
“…24,25 In studies involving colorectal resections, trainees performing surgery with the consultant mentors assisting have been shown to yield non-inferior outcomes when compared to consultants performing the surgery themselves. [26][27][28][29] A survey of surgeon mentors also found that the ASU allowed more time for education and was beneficial for surgical training of juniors. 30 Several other studies also found that increased consultant presence increased registrar case load and satisfaction.…”
Section: Egs Should Be Consultant Ledmentioning
confidence: 99%
“…Borowski et al 12 Chester and Britton 15 Costantino et al 29 Dalton et al 17 Hawkins et al 21 Hilska et al 19 Isbister 13 Khan et al 30 Krishna et al 16 Langhoff et al 23 Li et al 14 Pastor et al 22 Renwick et al 18 Singh and Aitken 25 Tytherleigh et al 24 Verheijen et al 26 Total Heterogeneity:…”
Section: Referencementioning
confidence: 99%